Assessment of Pseudoaffinity Chromatography Using Textile Dyes for Isolation of Buffalo Pituitary Luteinizing Hormone. (16th December 2012) - Arora, Taruna; Patel, Pankaj; Muralidhar, K.
Abstract : Extensive investigation has been carried out to elucidate the mechanisms involved in pseudoligand affinity chromatography using textile dyes, and, empirically, it has been attributed to the chemical and steric structures of dye and protein. Possibly, a variety of interactions especially ionic and/or hydrophobic influence with a varying share in the binding and differ from protein to protein and from dye to dye. In this study, we have attempted to understand the effect of various biophysical parameters like the nature of the eluant, pH, and ionic strength on the binding of crude luteinizing hormone (LH) with various triazine-based dyes and thus predict their nature. Based on the elution patterns, cibacron and reactive brown suggested a dual electrostatic and hydrophobic nature. Reactive blue and reactive yellow reflected a major electrostatic/ionic nature with yellow offering 50-fold purification in a single step, while reactive red and reactive green had a predominant hydrophobic nature. Appreciably, reactive red was binding LH very tightly unlike other dyes, and addition of the arginine in the elution buffer substantially weakened the protein-dye interactions. pH was observed to be a principal factor assisting the protein-dye binding as well as hydrophobicity of the dye and the proteins.